Rezension von: Walter, Robert u.a., Wiesenbach - Rothmund, Albert (Württembergisch Franken, 1985)
Robert Walter, Fritz Rummel, E. Langenbucher: Wiesenbach - Dorf in Hohenlohe-Franken. Ein Heimatbuch. 2. Aufl. 1983. 274, 50S.